Kajian Etnobotani Pemanfaatan Tumbuhan Obat untuk Gangguan Pencernaan di Desa Srimulyo, Malang - Niken Ayu Azzahra; Nayla Salsabilah Ramadhani; Diah Ayu Ramadani; Robiatun Mofarrohah; Fahrul Ghani Muhaimin; Syifa Nabila Firdausya; Heni Refdiana; Anas Bagaskara Witanto; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Susriyati Mahanal (Biocaster : Jurnal Kajian Biologi, 2026)
The purpose of this study was to identify and document the diversity of medicinal plants used by the people of Srimulyo Village, Dampit District, Malang Regency, which is still on the slopes of Mount Semeru. This study used a mixed method with a sequential exploratory design. Qualitative data were obtained through interviews with key informants and additional informants, while quantitative data were obtained through questionnaires to 98 respondents. Informants were selected using purposive sampling and snowball sampling which were analyzed qualitatively and quantitatively using the Informant Consensus Factor (ICF) index, Relative Frequency of Citation (RFC), Use Value (UV) analyzed from Species Use Value (SUV), Plant Part Use Value (PPUV) and Family Use Value (FUV), as well as Fidelity Level (FL). The results of the study identified 15 plant species from 10 families used to treat digestive disorders, with the dominant family Zingiberaceae (FUV=2.27) and the highest use value in Zingiber officinale (SUV=1.23). Leaves are the most widely used part of the plant (35.14%), generally through boiling. The ethnobotanical index shows a high consensus of use in typhoid fever (ICF=1.00) and constipation (ICF=0.98), with Psidium guajava as the most frequently mentioned species (RFC=0.78). Several species such as Musa sp., Cymbopogon citratus, Colocasia esculenta, Carica papaya, Piper retrofractum, and Strobilanthes crispus show absolute specificity of use (FL=100%). This ethnobotanical data directly contributes to local knowledge conservation efforts while strengthening the biocultural resilience of communities in adapting to the environment on the slopes of Mount Semeru from generation to generation.